Catalytic conversion of diformylxylose to furfural in biphasic solvent systems - Huang, Lizhen; Bian, Zelun; Li, Dalin; Cheng, Xin; Luo, Xiaolin; Shuai, Li; Liu, Jing (Frontiers in Bioengineering and Biotechnology, 2023)
Biobased furfural is a sustainable alternative to petrochemical intermediates for bulk chemicals and fuel production. However, existing methods for converting xylose or lignocelluloses in mono-/bi-phasic systems to furfural involve nonselective sugar isolation or lignin condensation, limiting the valorization of lignocelluloses. Herein, we used diformylxylose (DFX), a xylose derivative formed during the lignocellulosic fractionation process with formaldehyde protection, as a substitute for xylose to produce furfural in biphasic systems. Under kinetically optimized conditions, over 76 mol% of DFX could be converted to furfural in a water-methyl isobutyl ketone system at a high reaction temperature with a short reaction time. Finally, the isolation of xylan in eucalyptus wood as DFX with formaldehyde protection followed by converting DFX in a biphasic system gave a final furfural yield of 52 mol% (on the basis of xylan in wood), which was more than two times of that without formaldehyde. Combined with the value-added utilization of formaldehyde-protected lignin, this study would enable the full and efficient utilization of lignocellulosic biomass components and further improve the economics of the formaldehyde protection fractionation process.